Kagome-fiber prism compressor combination for Yb:KGW laser pulse compression to sub-40 fs. (25th January 2019) - Mayer, Dennis; Matthaei, Christian T; Heuer, Axel; Gühr, Markus
Abstract: Spectral broadening in hollow-core fibers is an important tool for pulse compression of low-peak power laser pulses, especially for Yb-based lasers. Here, we present a pulse compression scheme to reduce the pulse duration of a commercial Yb:KGW laser operating at 100 kHz repetition rate and 40 μ J pulse energy from 390 to 38 fs. The spectral broadening is accomplished using a krypton-filled Kagome-type fiber. We report broadened spectra for variable Kr-pressures and input powers. At optimal settings of 8 bar Kr-pressure and 3.3 W input power, the bandwidth of the pulse at the −10 dB level increased from 9.5 to 85 nm corresponding to a Fourier limit of 26 fs. A simple SF10 prism compressor is used to reduce the accumulated chirp and shortens the fiber output from about 500 to 38 fs. In addition to the spectral broadening, a pressure dependent change of the polarization is observed.